International Submarine Cables and Biodiversity of Areas Beyond National Jurisdiction The Cloud Beneath the Sea - Burnett, Douglas R. (Brill Research Perspectives, 2017)
In International Submarine Cables and Biodiversity of Areas Beyond National Jurisdiction, Douglas R. Burnett and Lionel Carter closely examine the relationship between trans-oceanic submarine cables and biodiversity in areas beyond national jurisdiction. Readership: All practitioners and academics interested in submarine cables, International Law of the Sea, and marine biodiversity law.